African Refugees in Israel: Beyond the Margins - Daniele, G. (The Current Refugees Crisis and Beyond: Narratives and Itineraries, 2016)
Since 1948, with the establishment of the state of Israel and the Palestinian Nakba (Catastrophe), the refugee question has become one of the major issues debated not only in the historic Palestine, but also in many countries across the world. Afterwards, other waves of refugees, along with their struggles and demands, have characterized the history of the Jewish state. Accordingly, this paper aims at analyzing the current situation of the most recent waves of African refugees from Sudan and Eritrea, and, in particular, their role within the heterogeneous panorama of Israeli social and political activism.